# Solve for b. A = 1/2ha + 1/2hb

*print*Print*list*Cite

### 2 Answers

First step is to isolate the term with b, by subtracting the term 1/2ha from each side of the equation because 1/2ha is attached to 1/2hb by addition.

A =1/2ha + 1/2hb

-1/2ha -1/2ha

A-1/2ha=1/2hb.

Now we have to separate b from 1/2h. Since the terms are connected by multiplication we use the opposite operation, division, to separate them

`(A-1/2 ha)-:(1/2 h) = (1/2 hb)-:(1/2 h)`

This yields `b=A/(1/2 h) - a` that's the equation solved for b. Simplifying the equation we get `b=(2A)/h - a`

`A=(1/2)ha+(1/2)hb`

factor out

from right side ,we have ,

`A=(1/2)h(a+b)` ,multiply both side by 2

`2A=h(a+b)` ,divide both side by h

`(2A)/h=a+b` , add -a both side

`(2A)/h-a=b`

`b=(2A)/h-a`

ans.